1994
DOI: 10.1007/bf02917339
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in normal and diabetic whole blood by neutron activation analysis

Abstract: The concentration of 10 trace elements in samples of normal and diabetic whole blood were investigated by neutron activation analysis (NAA). Instrumental NAA (INAA) was used for determination of Co, Cr, Hg, Rb, Se, and Zn, whereas NAA with radiochemical separation (RNAA) was employed for determination of Al, Cu, Mg, and Mn. The results for normal blood compare well with literature values. Co, Cr, Se, and Zn show lower values in diabetes than in the normal blood samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…To our knowledge, there is no information about CrHis supplementation on trace element distribution in liver and kidney tissues of diabetic animals. However, these results are consistent with previous studies that diabetes decreases Cr, Zn, Mn, and Se and increases Cu and Fe in human and animals [5,26]. Kazi et al [30] reported that the mean values of Zn, Mn, and Cr were significantly reduced in blood and scalp hair samples of diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, there is no information about CrHis supplementation on trace element distribution in liver and kidney tissues of diabetic animals. However, these results are consistent with previous studies that diabetes decreases Cr, Zn, Mn, and Se and increases Cu and Fe in human and animals [5,26]. Kazi et al [30] reported that the mean values of Zn, Mn, and Cr were significantly reduced in blood and scalp hair samples of diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies found that hyperglycemia was corrected by long-term Cr supplementation [10,17,18], while some could not find hypoglycemic effects [24,25]. Lower levels of Cr, Zn, and Se and higher Cu levels were found in patients with diabetes [5,22,26]. In the present study, a significant increase in levels of glucose and decrease in body weight and levels of Cr, Zn, Se, Mn was found in serum, liver, and kidney tissue of diabetic rats when compared to control rats.…”
Section: Discussionmentioning
confidence: 94%